The PROCESS 2020 Guideline: Updating Consensus Preferred Reporting Of CasESeries in Surgery (PROCESS) Guidelines. (December 2020) - Agha, Riaz A.; Sohrabi, Catrin; Mathew, Ginimol; Franchi, Thomas; Kerwan, Ahmed; O'Neill, Niamh; ,; Thoma, Achilles; Beamish, Andrew J.; Noureldin, Ashraf; Rao, Ashwini; Vasudevan, Baskaran; et al.
Abstract: Introduction: The PROCESS Guidelines were first published in 2016 and were last updated in 2018. They provide a structure for reporting surgical case series in order to increase reporting robustness and transparency, and are used and endorsed by authors, journal editors and reviewers alike. In order to drive forwards reporting quality, they must be kept up to date. As such, we have updated these guidelines via a DELPHI consensus exercise. Methods: The updated guidelines were produced via a DELPHI consensus exercise. Members from the previous DELPHI group were again invited, alongside editorial board members and peer reviewers of the International Journal of Surgery and the International Journal of Surgery Case Reports. An online survey was completed by this expert group to indicate their agreement with proposed changes to the checklist items. Results: A total of 53 surgical experts agreed to participate and 49 (92%) completed the survey. The responses and suggested modifications were incorporated into the previous 2018 guidelines. There was a high degree of agreement amongst the PROCESS Group, with all but one of the PROCESS items receiving over 70% of scores ranging 7–9. Conclusion: A DELPHI consensus exercise was completed and an updated and improved PROCESS Checklist is now presented. Highlights: This was a DELPHI consensus exercise to update the PROCESS guidelines. Of the invited surgical experts, 49 (92%) completed the survey. There was a high level of agreement in the PROCESS Group. The survey responses were incorporated as modifications and an improved PROCESS Checklist is now presented for use.